2000
DOI: 10.1002/(sici)1097-4628(20000321)75:12<1522::aid-app11>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Structure-property relationships of degradable polyurethane elastomers containing an amino acid-based chain extender

Abstract: A series of degradable polyurethanes of variable soft segment chemistry and content were synthesized and characterized. An amino acid-based diester chain extender was used to confer degradability and both polycaprolactone diol (PCL) and polyethylene oxide (PEO) were used as soft segments. In addition, the diisocyanate component was a potentially nontoxic diisocyanate (2,6-diisocyanato methyl caproate, LDI). The physicochemical properties of these unique series of polyurethanes were investigated. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(186 citation statements)
references
References 37 publications
(40 reference statements)
13
159
1
Order By: Relevance
“…PUR scaffolds prepared from the 1800 g mol −1 (600 g eq −1 ) polyol had T g values ~20°C higher than those prepared from 900 g mol −1 (300 g eq −1 ) polyol, which is consistent with the effects of soft segment equivalent weight on T g observed previously for segmented PUR elastomers prepared from LDI (40,41). The addition of PEG also reduced the T g of the PUR networks, which is attributed to the lower T g of PEG relative to the polyester polyols.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PUR scaffolds prepared from the 1800 g mol −1 (600 g eq −1 ) polyol had T g values ~20°C higher than those prepared from 900 g mol −1 (300 g eq −1 ) polyol, which is consistent with the effects of soft segment equivalent weight on T g observed previously for segmented PUR elastomers prepared from LDI (40,41). The addition of PEG also reduced the T g of the PUR networks, which is attributed to the lower T g of PEG relative to the polyester polyols.…”
Section: Discussionsupporting
confidence: 89%
“…The high compression set of LDI-based PUR scaffolds is conjectured to result from the absence of physical crosslinks in the polymer network, as evidenced by the lack of hydrogen-bonded urethane and urea groups in the hard segment (32). For segmented PUR elastomers synthesized from LDI, the microphase morphology depends on the molecular weight of the soft segment (40,41). For LDI elastomers incorporating a 2000 g mol −1 poly( -caprolactone) (PCL) diol soft segment, the value of T g was −52°C, which is close to that of pure PCL diol.…”
Section: Discussionmentioning
confidence: 88%
“…However, due to obstacles encountered during the synthesis and purification of such monomers, we initially focused on an easily synthesizable soft phase. Diene versions of polyoxyethylene are well known and have found wide application as soft phase segments, [80][81][82][83][84][85][86][87] while this soft phase is not siloxane based the synthesis of these dienes are trivial and can be produced in large quantities. Treatment of a representative bromoalkene with a glycolic alkoxide yields analytically pure monomer 9 after purification.…”
Section: Resultsmentioning
confidence: 99%
“…BioPUs and PUUs based on PCL and BDI have proved to be biocompatible in vivo and to have appropriate mechanical properties [74]. Skarja and Woodhouse [18,75,76] have developed biodegradable segmented PUs based on PCL or PEO macrodiol as the soft segment, with hard segments based on a phenylalanine diester chain extender and L-lysine diisocyanate (LDI). The results of the characterization show that the degradation rate and mechanical properties of these materials can be optimized by blending PCL-and PEO-based PUs.…”
Section: Polyester Soft Segmentsmentioning
confidence: 99%
“…Also, the use of chain extenders based on amino acids in BioPUs in order to improve biodegradability mediated by enzymes has been reported [18,75,76]. Caracciolo et al [20] reported the preparation of two series of biomedical segmented polyurethanes (SPU) based on PCL, HDI or LDI and three different chain extenders.…”
Section: Hard Segmentsmentioning
confidence: 99%